Thermal and Mechanical Properties of SK One Component Polyurethane (SKOCP). Determining the Thermal and Mechanical properties of SKOCP in Colder Conditions - Eidesen, Hans-Kristian Norum (UiT The Arctic University of Norway, 2017)
Polymers have an extreme wide range of potential applications. From artificial heart valves, computer hardware, coating materials, noise damping materials and so on. Polyurethane is one of the such materials with a broad range of applications. A few such applications and properties are, but not limited to, treatment of leakage of an expansion joint, abrasion resistance, anti-freezing performance and so on (Zhiheng, 2015). Additionally, the fish farm industry uses feed pipes and cages made of polyurethane. The Norwegian oil and gas industry have their eyes set on the Arctic region of the Norwegian continental shelf. If polyurethane is to be used in such conditions, knowledge on how the material changes it properties is needed. Properties that are expected to change are tensile properties, ice adhesion, thermal conductivity and more. The master thesis focuses on two aspects, namely mechanical and thermal properties of SK One Component Polyurethane (SKOCP). The SKOCP samples are provided by China Institute of Water Resources and Hydropower Research, Beijing, China. There are two different variants known as anti-seepage and anti-abrasion. The thesis is divided into three parts. First part focuses on determining the Young’s moduli. Second part investigates ice adhesion, and the third part investigates the thermal properties of SKOCP.